ANALISIS PENGARUH JUMLAH INDUSTRI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP JUMLAH PENDUDUK MISKIN DI KABUPATEN/KOTA PROVINSI BANTEN TAHUN 2012-2016 - Rio Dwi Heriansyah; Ida Nuraini; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2018)
Abstract: Title: "Analysis of the Influence of the Number of Industry and Human Development Index on the Number of Poor People in the Regency / City of Banten Province 2012-2016". The purpose of this research is to analyze poverty as well as to analyze the influence of industry variable and human development index on the number of poor people in Banten regency / city. The analysis tool used is panel data regression analysis. Based on the analysis of the number of poor people in Banten province still shows a high poverty rate. From the results of the study it can be explained that the variable number of industries has a negative and significant effect on poverty with an F-statistic value of 13.24154 and T-statistics of 3.354906, and the human development index variables have a positive and significant effect on the number of poor people with F- statistics of 13.24154 and T-statistics of 5.040772.Keywords: index of human ,industry, poor.